Revenue Experience as a Guide to Asset Valuation. - Mobley, Sybil C. (The Accounting Review, 1967)
Abstract The article stresses that accounting for values should be viewed as reliable if it is accomplished within the framework of the same basic requirements, which have contributed to the reliability of cost data. In accounting for values to be realized by the specific enterprise, the continuity assumption renders irrelevant any value, which does not relate to managements plan, normal operations, and the specific market commanded by the firm. Hence, it is value to the owner, not value in general, that is of interest in this proposal; and this value is the amount, which the owner will realize from his assets in their planned use, not the amount for which others in the industry are buying similar or identical assets. Therefore, valuations based on economy or industry indexes are irrelevant to this analysis. The most vital issue in selecting a valuation basis is, therefore, one of determining whether the particular valuation basis depends on information to which we have present access that presumably holds the most valid relationship with the future flow of revenue.